Hong Kong: Social Imaginaries and Post-Colonial Identities in the Umbrella Revolution. - Salvador Leetoy; Daniel Lemus Delgado (Portes: Revista mexicana de estudios sobre la Cuenca del Pacífico, 2018)
The aim of this article is to analyse to what extent demands for democracy apropos of the Umbrella Revolution in Hong Kong are the result of postcolonial determinations. We suggest that this is part of social discourses founded on narratives of cultural difference, portraying a distinctive Hong Kong’s identity in contrast to Mainland China. Even though we recognise the influence of networked transnational movements in this movement, we establish that there is a postcolonial strategic essentialism guiding the demands for participatory democracy in Hong Kong.